Two Issues in Computer Ethics for Non-Programmers. - Wunderlich, Mark E. (International Journal of Applied Philosophy)
Two of the distinctive ethical issues that arise for computer users (as opposed to computer programmers) have to do with the file formats that are used to encode information and the licensing terms for computer software. With respect to both issues, most professional philosophers do not recognize the burdens that they impose on others. Once one recognizes these burdens, a very simple argument demands changes in the behavior of the typical computer user: some of the ways we use computers gratuitously impose significant burdens on others; it is wrong to impose significant burdens on others gratuitously; some of the ways we use computers are unethical.